Impacted Teeth and Mandibular Fracture - Metin, Murat; Şener, İsmail; Tek, Mustafa (European Journal of Dentistry, 2007)
Objectives: In this retrospective study, we measured the relationship between the presences of impacted or unerupted teeth in the mandible and mandibular fractures.Methods: The records and radiographs of 41 patients with mandibular fracture associated with impacted or unerupted teeth were examined. The presence of impacted or unerupted teeth were assessed for each patient and related to the occurrence of fractures of mandible.Results: Patients with fracture in the impacted or unerupted teeth area present had a 1,73 times greater chance of an mandibular fracture than patients with no fracture in the impacted or unerupted teeth area. There was a statistically significant variation in the risk for a mandibular fracture depending on impacted or unerupted teeth presence (x2=5.29, P< .05).Conclusion: The presence of an impacted or unerupted teeth significantly increases the likelihood of an mandibular fracture. (Eur J Dent 2007;1:18-20)
Keywords: Mandibular fracture; Impacted teeth; Unerupted teeth